2010
DOI: 10.1242/jcs.069963
|View full text |Cite
|
Sign up to set email alerts
|

SPICE – a previously uncharacterized protein required for centriole duplication and mitotic chromosome congression

Abstract: SummaryProper assembly and function of a bipolar mitotic spindle is crucial for faithful bidirectional chromosome segregation during cell division. In animal cells, the two poles of the mitotic spindle are organized by centrosomes, microtubule-organizing structures composed of a pair of centrioles surrounded by the so-called pericentriolar material. Proteomic studies have revealed a large number of centrosome proteins, but many remain uncharacterized. Here, we characterize SPICE, a protein that localizes to sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“…Drosophila CEP135 is dispensable for cartwheel formation but is required to maintain robust centriole architecture [35]. It is therefore tempting to speculate that the decrease in the number of centrioles after CEP120 or SPICE1 depletion may be due to the assembly of abnormal/ short procentrioles [23,25]. This would be consistent with a report demonstrating that CEP135-deficient cells have perturbed centriolar triplet MT organization [34].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Drosophila CEP135 is dispensable for cartwheel formation but is required to maintain robust centriole architecture [35]. It is therefore tempting to speculate that the decrease in the number of centrioles after CEP120 or SPICE1 depletion may be due to the assembly of abnormal/ short procentrioles [23,25]. This would be consistent with a report demonstrating that CEP135-deficient cells have perturbed centriolar triplet MT organization [34].…”
Section: Discussionsupporting
confidence: 77%
“…We originally identified CEP120 and SPICE1 as putative interacting proteins [23]. While both are required for centriole duplication [23][24][25], CEP120 also participates in neuronal nuclear migration [26], and its loss in planarians results in shorter centrioles [27]. Together, these data suggest that the association between SPICE1 and CEP120 might reflect a shared function in centriole biogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of either CPAP or CEP120 results in excessively long centrioles and their depletion abolishes this phenotype (Comartin et al 2013;Lin et al 2013b). CEP120 also interacts with SPICE1 that is required for centriole duplication, spindle formation, and chromosome congression (Archinti et al 2010). Depletion of SPICE1 also results in short procentrioles, although, in contrast to its partners, overexpression of SPICE1 does not cause centriole elongation (Comartin et al 2013).…”
Section: Centriole Elongationmentioning
confidence: 99%
“…The reasons for this are not entirely clear. However, our BioID data suggest that Aire may act in a multi-protein complex, including SPICE1 ( Archinti et al, 2010 ), Human Augmin Complex (HAUS) complex proteins (Haus5 and Haus8) and CLASP proteins (CLASP1 and CLASP2) ( Lawo et al, 2009 ; Bratman and Chang, 2008 ), which have all been reported to function in centrosome maturation/duplication and mitotic spindle organization. Removal of AIRE from the complex by gene knockout could result in a partially functional complex, while replacement with a dominant negative form like AIRE ΔLESLL could disrupt the conformation of that complex and cause a more complete loss of function, as have been shown before in other experimental systems ( Veitia, 2007 ; Papp et al, 2003 ).…”
Section: Discussionmentioning
confidence: 92%